PENGEMBANGAN PERANGKAT PEMBELAJARAN FISIKA PADA ELASTISITAS DAN HUKUM HOOKE - Valentino Toe; Ferdy Dungus; Tineke Makahinda (Charm Sains: Jurnal Pendidikan Fisika, 2020)
This study aims to develop and test the feasibility of learning tools products based on the Problem Based Learning (PBL) with experimental methods on Elasticity and Hooke's Law. This research uses a development research model by following the stages of Brog and Gall. This research was carried out in SMA N 2 Bitung in class XI MIPA 7 (Experimental Class) and class XI MIPA 6 (Control Class) which were implemented in the odd semester of the 2019/2020 academic year in September-December of 2019. Based on the results of the validity test from the Material Experts and Media Experts, these learning tools respectively reached 96.3% and 94.45% so that they were included in the highly valid criteria. Student responses about this product are 81% so the product is included in the criteria is very valid and worth using. Analysis of the data from the learning outcomes that have been done is Tcount > Ttable and it can be concluded that there are significant differences in the improvement of learning outcomes in Class XI MIPA 7 that used this product, so this research is good and feasible to use.